Neonatal Outcomes of Premature Infants Born to Women with the Novel Coronavirus (SARS-CoV-2) Infection: A Case Control Study - Yasa, Beril; Memur, Seyma; Ozturk, Dilek Y.; Bagci, Onur; Uslu, Sait I.; Cetinkaya, Merih (American Journal of Perinatology, 2021)
Objective Novel coronavirus disease 2019 (COVID-19) is a disease associated with atypical pneumonia caused by the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). The first cases of COVID-19 were reported in Wuhan at the end of 2019. Transmission usually occurs via infected droplets and close personal contact; the possibility of vertical transmission is still under debate. This retrospective study aimed to analyze clinical characteristics of premature infants born to mothers with symptomatic COVID-19 disease.Study Design This case control study compared the clinical and laboratory data of 20 premature infants born to mothers infected with SARS-CoV-2 with sex and gestational age–matched historical controls.Results The median gestational age and birth weight in both groups were similar. Respiratory distress developed in 11 (55.5%) infants in study group and 19 (47.5%) infants in control group. Mechanical ventilation and endotracheal surfactant administration rates were similar. Median duration of hospitalization was 8.5 (2–76) days in study group and 12 days in historical controls. Real-time reverse-transcription polymerase chain reaction tests (RT-PCR) of nasopharyngeal swab samples for SARS-CoV-2 were found to be negative twice, in the first 24 hours and later at 24 to 48 hours of life. No neutropenia or thrombocytopenia was detected in the study group. Patent ductus arteriosus, bronchopulmonary dysplasia, and necrotizing enterocolitis rates were similar between groups. No mortality was observed in both groups.Conclusion To the best of our knowledge, this is one of the few studies evaluating the clinical outcomes of premature infants born to SARS-CoV-2 infected mothers. There was no evidence of vertical transmission of SARS-CoV-2 from symptomatic SARS-CoV-2-infected women to the neonate in our cohort. The neonatal outcomes also seem to be favorable with no mortality in preterm infants.Key Points
Keywords: SARS-CoV-2; COVID-19; premature; newborn